PD-L2 expression in colorectal cancer: Independent prognostic effect and targetability by deglycosylation. (3rd July 2017) - Wang, Huanbin; Yao, Han; Li, Chushu; Liang, Lunxi; Zhang, Yao; Shi, Hubing; Zhou, Chongzhi; Chen, Yingxuan; Fang, Jing-Yuan; Xu, Jie
ABSTRACT: Colorectal cancer (CRC) is the second leading cause of cancer death worldwide, and immune checkpoint blockade therapy provides an opportunity for improving the outcome of CRC patients. Recent studies suggest that programmed death ligand-1 (PD-L1) is only expressed in 12% of CRCs. Here, we demonstrate that PD-L2 is expressed in approximately 40% CRCs, and its expression independently associates with poor survival of CRC patients. By detection of PD-L2 expression by immunofluorescence in 124 CRC cases with 10-y survival data, we found significant association between PD-L2 overexpression in cancer cells and worse overall survival (46.3 vs 69.1 mo; p = 0.0004). The association remained significant in multivariate COX regression analysis (hazard ratio = 2.778, 95% confidence interval [CI] = 1.668–4.627; p < 0.0001). In the validation CRC data set, significant association between PD-L2 overexpression and poor survival was supported by the univariate analysis (27.1 vs. 88.9 mo; p = 0.0002) and multivariate model (hazard ratio = 7.09, 95%CI 1.78–28.16; p = 0.005). Western Blot revealed strong induction of PD-L2 expression by interferon-γ (IFNγ) in CRC cells, and the mRNA levels of both genes were significantly correlated in CRC tissue samples. Suppression of glycosylation with tunicamycin caused a shift in molecular weight and significant decrease in the expression of PD-L2 protein. In conclusion, PD-L2 overexpression in CRC cells, under the regulation by IFNγ and glycosylation, associates with poor survival of patients with colorectal cancer. These findings highlight PD-L2 as a promising therapeutic target in CRC and suggest potential routes to control PD-L2 expression in CRC cells.